2007
DOI: 10.1111/j.1399-0012.2007.00768.x
|View full text |Cite
|
Sign up to set email alerts
|

Low incidence of secondary neoplasia after autotransplantation for lymphoproliferative disease: the role of pre‐transplant therapy

Abstract: To asses the real contribution of pre-transplantation treatment in the incidence of secondary neoplasia after autologous transplant for lymphoproliferative disorders, we used stringent inclusion/exclusion criteria. One hundred and forty-two patients out of 323 that underwent autologous transplantation for lymphoproliferative disorders were studied. The risk factors that were evaluated with univariate and multivariate analysis included: gender, sex, age, diagnosis, radiotherapy, and chemotherapy prior to condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Laurenti et al 21 evaluated the role of pre-transplant chemotherapy in the incidence of secondary malignancies after auto-HCT for indolent lymphoma. Out of 142 patients, 3 patients developed t-MDS/AML and use of fludarabine was found to be an independent risk factor for development of t-MDS/AML in both univariable and multivariable analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Laurenti et al 21 evaluated the role of pre-transplant chemotherapy in the incidence of secondary malignancies after auto-HCT for indolent lymphoma. Out of 142 patients, 3 patients developed t-MDS/AML and use of fludarabine was found to be an independent risk factor for development of t-MDS/AML in both univariable and multivariable analyses.…”
Section: Discussionmentioning
confidence: 99%
“…All other variables registered showed no difference including performance score. Many clinical trials in CLL have shown the combination of fludarabine and cyclophosphamide to have tolerable toxicity, 1315 however, the observed significant reduction in renal function may be due to latent myeloma specific kidney impairment. All serious adverse events were reported to The Trial Secretariat within one working day of discovery or notification of the event.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the stem cell toxicity has been supported by the observation that the risk for sMDS/AML was correlated to the use of fludarabine based on an unknown mechanism. 15 …”
Section: Resultsmentioning
confidence: 99%